Kinematic traits of an elite paralympic karateka: a case report - Bertozzi, F.; Zago, M.; Ciprandi, D.; Galvani, C.; Sforza, C. (The Journal of Sports Medicine and Physical Fitness, 2020)
Karate is a martial art that includes striking, kicking and punching techniques, and requires high levels of functional skills. Karate counts millions of practitioners worldwide and it is also spreading in Paralympic competitions: there is a need for accurate categories definition for disabled athletes. The aim of the current study was to present kinematic data of an elite Paralympic karateka, in comparison with able-bodied athletes, to promote a better classification within the discipline, based on objective evaluations of physical impairments. A male black belt Paralympic karateka (age: 36 years; body weight: 75.5 kg; height: 173 cm) with lower limbs impairments was evaluated. He performed a standardized sequence of movements (kata) from Shotokan karate. Joints and center-of-mass kinematics were collected with an optoelectronic motion capture system and compared with those obtained in two groups of able-bodied (Masters and Practitioners) athletes from a previous study. The sequence performed by the karateka lasted longer than in both able-bodied groups. Center of mass velocity and acceleration lowered in comparison with Masters. Knees range of movement and peak angular velocity were similar to Practitioners but lower than Masters. We concluded that physical impairments negatively affected the function of lower limbs in the Paralympic athlete, as fundamental skills in karate elite performance (dynamic balance control and joint angular velocity) were lower